-3b(2a-3b)+6(-6ab+25b)=

Simple and best practice solution for -3b(2a-3b)+6(-6ab+25b)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3b(2a-3b)+6(-6ab+25b)= equation:


Simplifying
-3b(2a + -3b) + 6(-6ab + 25b) = 0
(2a * -3b + -3b * -3b) + 6(-6ab + 25b) = 0
(-6ab + 9b2) + 6(-6ab + 25b) = 0
-6ab + 9b2 + (-6ab * 6 + 25b * 6) = 0
-6ab + 9b2 + (-36ab + 150b) = 0

Reorder the terms:
-6ab + -36ab + 150b + 9b2 = 0

Combine like terms: -6ab + -36ab = -42ab
-42ab + 150b + 9b2 = 0

Solving
-42ab + 150b + 9b2 = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-150b' to each side of the equation.
-42ab + 150b + -150b + 9b2 = 0 + -150b

Combine like terms: 150b + -150b = 0
-42ab + 0 + 9b2 = 0 + -150b
-42ab + 9b2 = 0 + -150b
Remove the zero:
-42ab + 9b2 = -150b

Add '-9b2' to each side of the equation.
-42ab + 9b2 + -9b2 = -150b + -9b2

Combine like terms: 9b2 + -9b2 = 0
-42ab + 0 = -150b + -9b2
-42ab = -150b + -9b2

Divide each side by '-42b'.
a = 3.571428571 + 0.2142857143b

Simplifying
a = 3.571428571 + 0.2142857143b

See similar equations:

| R=y | | -3b(2a-3b)+6(-6ab-25b)= | | 100[0.06(y+2)]= | | 4x+1=5x+(-5) | | -(x-9y)= | | 4x+1=5x+-5 | | 3log(x+2)=6 | | 6n+6=(n+8)-7n | | 1+sqrt(x+5)=sqrt(2x+5) | | (12a^4b-7a^2b^2+8ab^3)+(-6a^4b-5a^2b^2+3ab^3)= | | 2x-4+7=3 | | (x-4)(x-8)=5 | | 10x^2-3x=6x-8x^2 | | 2x-9=-6 | | 2+5(10)= | | (6x^2y-4xy^2)-(-9x^2y-7xy^2)= | | 2x^2-20x-5525=0 | | 100[0.06(n+10)]= | | 2b^3-4=r^8 | | 50x-4=45x+1 | | 2y^6+9=g^1 | | 50x-1=45x+1 | | -1x-6y=5 | | C-16=18 | | B+127=52 | | -x+6y=5 | | K+6K-13=57 | | 3x*3x-2x+7=0 | | 6-3-(-10)-7+(-13)+33= | | 58(w)(w+8)=x | | (3x-5)(x-2)=0 | | 8-5x-x=14 |

Equations solver categories